EFFECT OF ACID ADAPTATION AND DIFFERENT SALT CONCENTRATIONS ON SURVIVAL OF LISTERIA MONOCYTOGENES IN TURKISH WHITE CHEESE - İlhak, O. İrfan; Öksüztepe, Gülsüm; Calicioglu, Mehmet; Patir, Bahri (My University, 2011)
Survival of acid-adapted and nonacid adapted Listeria monocytogenes in Turkish white cheese with different salt concentrations (3.8 and 6.7% NaCl) was investigated. Cheese blocks were inoculated with L. monocytogenes and stored at 4C for 15 days. Samples were taken on different days and analyzed for the numbers of the pathogen, and the samples were challenged with simulated gastric fluid (SGF) for determining acid tolerance. There was no significant differences between the numbers of acid-adapted and nonadapted L. monocytogenes cells regardless of the salt concentration on sampling days (P > 0.05). Challenge in SGF revealed that there was no significant difference between acid-adapted and nonadapted bacteria in cheese with 3.8% NaCl throughout the storage period, while significant (P < 0.05) differences between those cells in cheese with 6.7% NaCl were found after day 5. These results suggest that acid-adapted L. monocytogenes exposed to high salt concentration such as 6.7% may have an advantage in SGF.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Acid adaptation; Listeria monocytogenes; White cheese; Salt concentration